2005
DOI: 10.1212/01.wnl.0000148477.65273.0c
|View full text |Cite
|
Sign up to set email alerts
|

MR tractography for the evaluation of functional recovery from lenticulostriate infarcts

Abstract: The corticospinal tracts (CSTs) crossed the lenticulostriate artery territory exclusively at the posterosuperior quadrant, and the degree of CST involvement within the infarcts was directly related to stroke severity and functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 24 publications
5
81
0
2
Order By: Relevance
“…Similarly, another study reported that the degree of CST involvement on DTT within 3 days of stroke onset was strongly correlated with the severity of motor deficit and functional recovery at 3 months in patients with an acute lenticulostriate infarct. 19 To our knowledge, ours is the first prospective study to examine consecutive patients with DTT within the first 12 hours after MCA stroke onset.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Similarly, another study reported that the degree of CST involvement on DTT within 3 days of stroke onset was strongly correlated with the severity of motor deficit and functional recovery at 3 months in patients with an acute lenticulostriate infarct. 19 To our knowledge, ours is the first prospective study to examine consecutive patients with DTT within the first 12 hours after MCA stroke onset.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the decrease in mean FA values correlated positively with the motor deficit at 30 days after stroke. 19 Combined involvement of the PLIC and CS or CR at day 30 was not significantly associated with decreased FA indexes (P ϭ 0.445 for the interaction between PLIC and CS; P ϭ .830 for PLIC and CR). Hence, axonal damage reflected as decreased FA ratio values at day 30 was also secondary to PLIC damage.…”
Section: Association Between the Region Of The Cst Affected In The Fimentioning
confidence: 85%
See 2 more Smart Citations
“…23,29) DTI can be used to measure diffusion anisotropy in vivo, and is a promising method for noninvasive detection of the degree of fiber damage in various disease processes affecting the white matter. 11,19) Fractional anisotropy (FA) as determined with DTI has been used to evaluate traumatic axonal injury, and the clinical utility of this technique has been described. 2) T2*GRE imaging is superior to T 1 -weighted, T 2 -weighted, and FLAIR imaging for the detection of hemorrhagic DAI lesions.…”
Section: Introductionmentioning
confidence: 99%